2021
DOI: 10.1007/s12035-021-02526-3
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Long Noncoding RNA Expression Profile in a Niemann-Pick C Disease Mouse Model

Abstract: Niemann-Pick type C (NP-C) disease is a neurodegenerative lysosomal storage disorder primarily caused by mutations in NPC1. However, its pathogenesis remains poorly understood. While mounting evidence has demonstrated the involvement of long noncoding RNAs (lncRNAs) in the pathogenesis of neurodegenerative disorders, the lncRNA expression profile in NP-C has not been determined. Here, we used RNA-seq analysis to determine lncRNA and mRNA expression profiles of the cerebella of NPC1−/− mice. We found that 272 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Most of these pathways with exception of small molecule biochemistry, vitamin metabolism and protein folding and refolding were found to be affected in npc1 Δ56/ Δ56 larvae. RNAseq analysis in NPC brain organoids showed that most of the gene differences were those related to nervous system development (Lee et al, 2020) RNAseq performed in cerebellum and astrocytes of an NPC mouse model (Cougnoux et al, 2021;Han et al, 2021) revealed most discrepancies with npc1 zebrafish model with altered pathways like immune system process, plasma membrane, protein binding, glutamate transporter, glycosphingolipid biosynthesis, TGF-beta signaling, protein digestion and absorption, cell adhesion molecule, and neuroactive ligand-receptor interaction pathways. Only immune system process, plasma membrane and cell adhesion pathways were altered in npc1 Δ56/ Δ56 larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these pathways with exception of small molecule biochemistry, vitamin metabolism and protein folding and refolding were found to be affected in npc1 Δ56/ Δ56 larvae. RNAseq analysis in NPC brain organoids showed that most of the gene differences were those related to nervous system development (Lee et al, 2020) RNAseq performed in cerebellum and astrocytes of an NPC mouse model (Cougnoux et al, 2021;Han et al, 2021) revealed most discrepancies with npc1 zebrafish model with altered pathways like immune system process, plasma membrane, protein binding, glutamate transporter, glycosphingolipid biosynthesis, TGF-beta signaling, protein digestion and absorption, cell adhesion molecule, and neuroactive ligand-receptor interaction pathways. Only immune system process, plasma membrane and cell adhesion pathways were altered in npc1 Δ56/ Δ56 larvae.…”
Section: Discussionmentioning
confidence: 99%
“…These disorders are extremely rare and for most of them the implication of lncRNAs is yet to be investigated. Indeed, no evidence is currently available linking lncRNAs with Batten disease and metachromatic leukodystrophy, but indications are emerging connecting these molecules to SMA and NPD [68,69].…”
Section: Lncrnas In Pediatric Neurodegenerative Diseasesmentioning
confidence: 99%
“…Symptoms can range from hepatosplenomegaly (enlarged liver and spleen) to neurological manifestations such as developmental regression, loss of motor skills, and intellectual decline [67]. Again, evidence linking lncRNAs to NPD disease is limited, but RNA-sequencing could be helpful towards this goal and one recent study was performed in the cerebellum of a murine model of NPD [69]. This study highlighted 272 dysregulated lncRNAs in NPD, and amongst them, lncRNA H19 was selected for further characterization [69].…”
Section: Lncrnas In Pediatric Neurodegenerative Diseasesmentioning
confidence: 99%
“…RNAseq performed in cerebellum and astrocytes of an NPC mouse model (Cougnoux et al, 2021;Han et al, 2021) revealed most discrepancies with npc1 zebrafish model with altered pathways like immune system process, plasma membrane, protein binding, glutamate transporter, glycosphingolipid biosynthesis, TGF-beta signaling, protein digestion and absorption, cell adhesion molecule, and neuroactive ligand-receptor interaction pathways. Only immune system process, plasma membrane and cell adhesion pathways were altered in npc1 Δ56/ Δ56 larvae.…”
mentioning
confidence: 91%